Data protection in the European Union 2 - Krajewska, Atina (Henry Stewart Talks, 2015)
Genetic data processing in the various European institutions, Further processing of data beyond initial purpose, The right to request erasure of personal information, Formalities and penalties, Extraterritoriality and international data transfer